Al-Ijmā‘ fī al-Tafsīr dalam Perspektif Mufasir Modern: Telaah Surah al-Kahf [18]: 60 dan al-Layl [92]: 17 - Amru, Khobirul; Kholid, Abd.; Iwanebel, Fejrian Yazdajird (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
The existence of al-Ijmā‘ fī al-Tafsīr  as a new discourse which officially incorporates to the study of Uṣūl al-Tafsīr has evoked various questions. The problem seems to lie within the episteme of the discourse which eventually conflicted to the reform spirit of modern Qur’anic exegetes. This study aims at trailing a constituted concept of al-Ijmā‘ fī al-Tafsīr through the eyes of six modern Qur’anic exegeses written by Bint al-Shāṭi’, Sayyid Quṭb, Abū Zahrah, Muḥammad al-Ghazālī, ‘Ābid al-Jābirī and ‘Izzat Darwazah. It begins with analyzing the Qs. al-Kahf [18]: 60 and Qs. al-Layl [92]: 92, as the interpretation of these two verses is stated as a definitive interpretation, which is agreed upon by some commentators (mujma‘ ‘alayh). This paper proves that the discourse of al-Ijmā‘ fī al-Tafsīr has not received enough acceptance or serious attention by most modern commentators. The six modern exegetes also stand on different outlook for the consensus of Qur’anic interpretation: some exegetes quote and admit it; some of them do not cite for certain reasons; and one of them rejects and doubts it.